Methods to Suppress Earlier Leakage in 200V Superjunction LIGBT on Partial SOI - Kho Ching Tee, Elizabeth; Alexander, Hölke; Steven John, Pilkington; Deb Kumar, Pal; Ng, Liang Yew; Wan Azlan, Bin Wan Zainal Abidin; Marina, Antoniou; Florin, Udrea (ENCON 2013, 2013)
For most devices fabricated on SOI wafer, there is a consideration of backside coupling effect. This phenomenon becomes catastrophic if the device fabricated on the SOI wafer is an IGBT which consists of n-p-n-p structure and employs both the partial SOI and DTI technique. Earlier leakage had been found during development of 200V superjunction lateral IGBT (SJ LIGBT) that fabricated on SOI wafer. The purpose of this work is to identify the root cause and propose the solutions. This is done by 2D simulations and the proposed solution had successfully solved the earlier leakage problem and yield high breakdown voltage of 220V.